Strategi Negosiasi Nabi Muhammad Saw. pada Perjanjian Hudaibiyah dalam Perspektif Analisis Pentad - Dhanny Wahyudiyanto (INTELEKSIA - Jurnal Pengembangan Ilmu Dakwah, 2022)
Conflict must be handled properly so that it is not destructive for dawah organization. One of the ways to handle conflicts is through negotiation. One of the negotiations that was quite phenomenal in Islamic history was the negotiation that the Prophet carried out with the Quraysh in the Hudaibiyah agreement. In the agreement, the Prophet seemed very accommodating and gave in to the Quraysh. Even some of the companions were disappointed with the treaty principal agreed upon by the Prophet. However, unexpectedly, the implications of the agreement have a positive value for the development of Islam. How the negotiation strategy carried out by the Prophet in the agreement can be a lesson for managers / da'wah activists if later they are faced with conflict and require them to negotiate. The negotiation strategy carried out by the Prophet in this paper will be described through the theory of Dramatism conceptualized by Kenneth Burke. This paper that uses the pentad analysis method finds that the negotiation efforts carried out by the Prophet through the Hudaibiyah agreement lead to the goal of focusing the Islamic da'wah agenda peacefully, and taking the opportunity to minimize the threat of attacks on both sides of the city of Medina at one time.